تحديات المعاهد التقليدية الإسلامية في تعليم اللغة العربية في عصر 5.0 - الشاطبي, علاء النجيب; أنجو, فابيلا نيماس ويداري; المفتوحة, نورية; الحلم, مستفق (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
The Development of Arabic Language in the Era of 5.0 Presents a Challenging Task for Pesantren salafs As a Pesantren salaf that emphasizes the acquisition and advancement of knowledge and skills in Arabic, these institutions face unique challenges in developing Arabic language education during the Era of 5.0. The objective of this research is to describe the challenges of Arabic language education in Pesantren salafs during this era. This study is qualitative in nature, utilizing a bibliographic approach. The data was gathered from books and journals. The results of this study indicate that one of the challenges facing Pesantren salafs in Arabic language education is the weakness of students in speaking Arabic. As the result, in pesantren salaf, the development of Arabic language learning in facing challenges in the 5.0 era includes technology integration, interactive approaches, and curriculum adjustments. Difficulties arise due to rapid changes in technology, requiring the adaptation of students and teachers to new learning methods. Traditional factors such as limited resources and lack of access to technology can be additional obstacles, increasing the complexity of Arabic language learning in Salaf huts in the face of the 5.0 era.